Physicochemical and functional properties evaluation of the river fish protein concentrate gel as a function of the pH of the process (Nexo Revista Científica, 2021)
The CPP fish protein concentrate is the muscle of the shredded fish, free of bones, skin, dark meat and bones, which is washed several times with water and drained to the original water proportion, leaving what could be called the functional material or "surimi". The objective of this work was to determine how the variation of the pH and the composition of the wash water affected the CPP samples from the muscle of “sabalo” (Prochilodus platensis). The macrocomponents studied were total proteins, total fat, moisture, total ash, and resistance, color and water retention capacity (CRA) of the gels obtained from the CPP of tarpon. The resistance of the CPP gel resulted in significant differences for all treatments at p